2018
DOI: 10.1177/2050640617745459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of submucosal injection in endoscopic papillectomy of ampullary tumor: Propensity‐score matching analysis

Abstract: Background: The role of submucosal injection (SI) in endoscopic papillectomy (EP) is controversial. Objective: This study investigated the effects of SI before EP of ampullary tumors. Methods: All patients who underwent initial curative EP at our institution between March 2006 and March 2014 were retrospectively recruited. The presence of residual tumor after three months, recurrence-free survival and post-procedural adverse events were compared between the SI group and non-injection (NI) group. Propensity-sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 33 publications
(68 reference statements)
1
19
0
1
Order By: Relevance
“…After screening of titles and abstracts, 367 studies remained. Finally, 59 papers were eligible to be included into the meta-analysis after full-text evaluation (42 EA, 8 SA, 1 PD, 3 SA + PD, 4 EA + SA, 1 EA + PD; Figure 1 PRISMA chart) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening of titles and abstracts, 367 studies remained. Finally, 59 papers were eligible to be included into the meta-analysis after full-text evaluation (42 EA, 8 SA, 1 PD, 3 SA + PD, 4 EA + SA, 1 EA + PD; Figure 1 PRISMA chart) [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ...…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in 40.4% of patients with EA, a prior submucosal injection was performed to lift the lesions. A submucosal injection is not recommended as such injection resulted in reduced rates of complete resection [10,31,41,80]. Furthermore, in some EA studies, additional therapy by radiofrequency ablation (RFA), argon plasma coagulation (APC), additional EA or surgery was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The arguments for the use of submucosal injection are a reduction in the risk of bleeding when associated with adrenaline, besides the creation of a cushion with separation of the superficial and deep layers. However, this has been abolished by many centers because it increases the difficulty of grasping the lesion and the risk of pancreatitis (21) . In our series, submucosal injection with a saline solution containing adrenaline was used in only two procedures.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study compared the clinical outcomes of endoscopic papillectomy with and without submucosal injection and concluded that routine submucosal injection is associated with more frequent residual tumor and shorter recurrence-free survival, without reducing post-procedural adverse events. 38 Polypectomy snares. No superiority has either been proven between different materials for polypectomy snares, although in most reports, standard braided stainless steel wire have been used.…”
Section: General Principlesmentioning
confidence: 99%
“…A recent study compared the clinical outcomes of endoscopic papillectomy with and without submucosal injection and concluded that routine submucosal injection is associated with more frequent residual tumor and shorter recurrence-free survival, without reducing post-procedural adverse events. 38…”
Section: Eamentioning
confidence: 99%